Research on Case-Based Teaching of Digital Image Processing Implemented with Python Language - Xiong, Taisong; Yang, Zhipeng; Liu, Tao; Zhao, Yifei (Scholars Journal of Arts, Humanities and Social Sciences, 2024)
Digital image processing is a course with strong theoretical backgrounds and also has wide applications in reality. However, traditional teaching method only focuses on delivering abstract theories, which leads to a decrease in students' interest in the course. To resolve this problem, this paper studies the characteristics of basic image processing algorithms from the perspective of combining theory with practice. We investigate the characteristics of fundamental image processing algorithms. We implement some teaching cases using Python.